건설현장 위험영향요소 기반의 위험도 산정 방법론 - 이현수; 김현수; 박문서; 이광표; 이사범; Lee, Hyun-Soo; Kim, Hyun-Soo; Park, Moon-Seo; Lee, Kwang-Pyo; Lee, Sa-Bum (한국건설관리학회 논문집, 10(6), 2009)
Many work-related risk factors can cause construction site hazards. Considering variable and changeable characteristics of construction site, risk of same trade can be different by combination of inherent characteristics. But established safety management has performed like other industries not reflecting characteristics of construction. So, to suggest risk assessment methodology considering risk influence factors in construction site, this study extracts risk influence factors by literature reviews and surveys, builds the weighting system for classification of factors. And risk of trade is calculated based on frequency and severity of risk. Risk assessment methodology is suggested by integrating risk influence factors and risk of trade. From this, risk considering the conditions of construction sites can be derived and based on the derived risk, safety management can be performed more effectively. This study has meaning for assessing the risk which can reflect characteristics of construction site considering risk influence factors. 건설 산업에 내재된 위험은 작업환경, 작업의 종류, 작업자의 특성 등이 결합되어 발생한다. 건설 현장의 가변적이며 유동적인 특성을 고려한다면 동일 공종이라도 내재된 특성들의 조합에 따라 위험의 크기가 다르게 나타날 수 있다. 하지만 기존의 안전 관리 방식은 이러한 건설업의 특성을 반영하지 못한 체 타산업과 유사한 안전 관리를 수행하고 있다. 이에 본 연구는 건설현장의 다양한 위험 요소를 고려한 위험도 산정 방법을 제시하기 위해 선행연구 분석 및 설문을 통해 위험 영향 요소를 도출하고 가중치 체계를 구축하였다. 그리고 빈도와 강도 기반의 공종별 위험도를 구하였다. 위험 영향 요소와 공종별 위험도를 결합하여 건설 현장의 상황에 맞는 위험도 산정 방법을 마련하였다. 이로써 건설 현장의 특성을 고려한 위험도를 구할 수 있으며, 위험도를 바탕으로 보다 효과적인 안전관리활동을 펼칠 수 있을 것이다. 따라서 본 연구는 위험 영향 요소들을 고려하여 현장 특성을 반영한 위험도를 산정하였다는데 그 의미가 있다.